The Role of Health Protective Effect in the Food Purchase of the Population - T. Nagy-Pető, Dorka (International Journal of Engineering and Management Sciences, 2019)
In our homecountry just like in other developing countries, civilization diseases can be realized not only as individual costs but also through social security expenditures and from the expenditure side of the national economy. The main risk factors for the spread of civilization diseases include inadequate food consumption, lack of physical activity and genetic conditions. The topic of this research is the role of health food in daily nutrition and in buying food for the population, which addresses current issues and concerns as described above.